Test Stand Dynamics Properties Investigation by Means of Simulation Computations - Valčáková, Lenka; Štefaňaková, Veronika (Manufacturing Technology Journal, 2015)
The paper is devoted to the mechanical system dynamic properties investigation of the test stand RAILBCOT (RAIL vehicles Brake Components Test stand). Using sensors attached to some parts, have been measured values of positions, the longitudinal, vertical and transversal forces, revolutions and accelerations. There was created computational model of the mechanical system in SIMPACK software system environment. There were performed model establishment, starting and boundary condition setting and simulation computations to determine the dynamic properties parameters. The measured values were compared with calculated values. Subsequent verification has been confirmed the necessity of modification of the flexible member of the bench. The paper consists of issue definition and the comprehensive references specification from the field of investigation of working team at the University of Žilina relevant to this field of study.
Keywords: test bench; multibody system dynamics; RAILBCOT; SIMPACK; simulation computations